Study of the mechanical performance and durability of mortars reinforced with treated and untreated cabuya fiber - Guerrero, Viviana (2021)
Currently, the cement industry causes great damage to the environment, generating immeasurable amounts of carbon dioxide (CO2). According to statistics, at least 8% of global CO2 emissions are caused by humans in the cement industry alone. Faced with this problem, there is a need to reduce contamination by incorporating natural fibers into the cement mixture, in order to obtain a more sustainable mortar, since this reduces the amount of cement. One of the intrinsic properties of mortar is its low tensile and flexural strength, which leads to limitations in structural applications. In order to improve the mechanical properties of the mortar and its durability, experimental designs will be established using different volume percentages of treated and untreated cabuya fibers, cement and zeolite. The tensile strength and flexural strength increased when using a percentage of 7.5% chemically treated cabuya fiber, 50% zeolite and 42.50%.